Culture of mature trophoblastic giant cells from bovine placentomes - Landim, L. P.; Miglino, M. A.; Pfarrer, C.; Ambrosio, C. E.; Garcia, J. M. (Elsevier B.V., 2007)
The mostly binucleate trophoblast giant cells (TGC) found in bovine placentomes, in addition to synthesizing and releasing hormones play an important role in fetal development and maternal adaptation to pregnancy. Placentomes from early gestation were collected, and for isolation of mature TGC, three cellular disaggregation methods, mechanical (MECH), enzymatic by trypsin (TRYP) or collagenase (COLL) were compared to each other. Further on, the cell survival in culture medium (DMEM) supplemented with either 10% fetal calf serum (FCS) or 10% serum replacement (SR) on culture plates free of any substrate was evaluated over a period of 90 days by trypan blue exclusion. The cells were further characterized by HOECHST 33342 nuclear staining, and immunocytochemical staining with monoclonal antibodies against vimentim and cytokeratin. A mean total rate of TGC survival of 82.56% was recorded. Statistical analysis showed significantly higher survival rates after enzymatic disaggregation with COLL (86.23%) than following MECH (80.38%) or TRYP (80.91%) treatment. Supplementation of DMEM with FCS resulted in significantly higher cellular survival rates (87.13%) when compared to the addition of SR (77.73%). Analysis of the influence of both, disaggregation method and medium supplementation on TGC survival revealed statistically significant differences between the following groups: MECH-SR (71.09%) was significantly lower than all other groups; TRYP-SR (78.03%) was significantly different from all other groups; TRYP-FCS (83.43%) and COLL-SR (84.08%) were significantly lower than MECH-FCS (89.98%) which together with COLL-FCS (88.25%) showed the highest cellular survival rate. In summary, our results show that TGC isolated from early gestation placentomes may be viable for more than 90 days of culture. However, whether these TGC produce placental lactogen throughout this period has yet to be determined. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cell culture; cell survival; Placenta; Bovine; trophoblast giant cell